Bridging Culture and STEM Education: Developing a Tamansiswa-Grounded Project-Based Learning Model to Strengthen Mathematical Connections and Collaboration Skills - Annis Deshinta Ayuningtyas; Sugiman; Kismiantini; Wahyu Setyaningrum (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and evaluate the initial feasibility of a culturally grounded STEM instructional model that incorporates the Tamansiswa educational philosophy, encompassing Tri N (Niteni, Nirokke, and Nambahi) and Tri Ko (Cooperative, Consultative, and Corrective), to scaffold project-based learning while fostering students’ mathematical connection and collaboration skills. Employing an Educational Design Research (EDR) approach, the study collected data through expert validation sheets, implementation observation sheets, response questionnaires, mathematical connection tests, and collaboration observation sheets. Expert validation was analyzed using Aiken’s V and feasibility percentages, while implementation fidelity was assessed using Interjudge Agreement (IJA). Effectiveness was evaluated using Normalized Gain (N-Gain) and, following Shapiro–Wilk normality testing, either the Wilcoxon signed-rank test with rank-biserial r or the paired-samples t-test with Cohen’s dz, as appropriate. The study comprised analysis, design, and evaluation phases, including validation by five experts and a small-scale pilot involving 30 eighth-grade students from two junior high schools in Yogyakarta. The model demonstrated very high validity (95.42%; Aiken’s V = 0.86–0.96) and good implementation fidelity (mean IJA = 89.49%). Statistically significant improvements were observed in students’ mathematical connection skills (Wilcoxon Z = 4.78, p < .001; rank-biserial r = 0.87; N-Gain = 0.44, moderate) and collaboration skills (t(29) = 14.62, p < .001; Cohen’s dz = 2.67; N-Gain = 0.41, moderate). These findings provide empirical evidence that indigenous educational philosophy can function as a coherent pedagogical foundation, rather than merely as supplementary cultural content, for integrated project-based STEM learning. The study also offers practical implications for curriculum developers seeking to design culturally responsive instructional frameworks.